The effect of white noise on sucking success and infant comfort in premature babies: a paired randomized controlled trial - Esra Tanrıverdi; Tülay Kuzlu Ayyıldız (Hygeia Press di Corridori Marinella, 2023)
Purpose: This study was conducted in a paired randomized controlled trial manner to determine the effect of white noise on sucking success and infant comfort in premature babies. Methods: Sixty-six preterm babies were randomized into two groups (33 newborns in the white noise group and 33 newborns in the control group). In the white noise group, preterm babies were exposed to white noise during breastfeeding. Patient identification form, application registration form, Premature Infant Comfort Scale (PICS), and LATCH Breastfeeding Assessment Tool were used in the study. Results: There was no significant difference between the pre- and post-procedure LATCH scores of the babies in the white noise and control groups (p > 0.05). However, in the comparison within the groups, a statistical difference was found between the pre- and post-procedure scores of the newborns in the white noise and control groups (p < 0.05). The breastfeeding success scores of the newborns in the white noise group were found to be higher than that of the control group (white noise group Cohen d value = 0.45, control group Cohen d value = 0.17). While there was no significant difference between the groups in terms of pre-procedure PICS scores (p = 0.114), a significant difference was found in the post-procedure PICS scores (p = 0.031). The increase in the comfort levels of newborns in the white noise group was found to be significant. Conclusion: The white noise played to premature babies during breastfeeding was effective on the sucking success and the comfort level.